Physicochemical and Microbial Analysis of Deep Well Water in Sitio Cabalawan, Barangay Rizal, Surigao City: Implications for Domestic Use and Health - Liwaya S. Longos (Tropical Aquatic and Soil Pollution, 2026)
Groundwater from deep wells was the primary source of domestic water for many rural communities in the Philippines. However, routine groundwater quality monitoring remained limited, increasing the risk of exposure to physicochemical and microbiological contaminants. This study evaluated the quality of untreated deep-well water in Sitio Cabalawan, Barangay Rizal, Surigao City, Philippines. Water samples were collected from three groundwater supply configurations: a communal hand pump, a household hand pump, and a household faucet supplied through an elevated storage tank. Physicochemical parameters, including temperature, pH, total dissolved solids (TDS), nitrate, and iron, together with microbiological indicators comprising heterotrophic plate count (HPC), total coliforms, and thermotolerant (fecal) coliforms, were analyzed using standard laboratory methods and compared with the Philippine National Standards for Drinking Water (PNSDW) and the World Health Organization (WHO) Guidelines for Drinking-water Quality. The results showed that pH, nitrate, and iron concentrations complied with both PNSDW and WHO standards, whereas TDS exceeded the PNSDW acceptable limit at two sampling sites. In contrast, microbiological analyses revealed elevated HPC in all samples, total coliforms at every sampling site, and fecal coliform contamination in water collected from the household storage and distribution system. These findings suggested that while groundwater chemistry remained generally acceptable, microbial contamination likely occurred during post-extraction storage and household distribution. The study concluded that untreated deep-well water was microbiologically unsuitable for direct human consumption despite meeting most physicochemical standards. The findings highlighted the need for routine groundwater monitoring, improved well protection, proper storage and distribution infrastructure, and household water treatment to reduce waterborne disease risks and support integrated groundwater quality management in flood-prone rural communities.